Nature of socioeconomic inequalities in neonatal mortality: population based study. (2nd December 2010) - Smith, Lucy K; Manktelow, Bradley N; Draper, Elizabeth S; Springett, Anna; Field, David J
Abstract : Objective To investigate time trends in socioeconomic inequalities in cause specific neonatal mortality in order to assess changing patterns in mortality due to different causes, particularly prematurity, and identify key areas of focus for future intervention strategies. Design Retrospective cohort study. Setting England. Participants All neonatal deaths in singleton infants born between 1 January 1997 and 31 December 2007. Main outcome measure Cause specific neonatal mortality per 10 000 births by deprivation tenth (deprivation measured with UK index of multiple deprivation 2004 at super output area level). Results 18 524 neonatal deaths occurred in singleton infants born in the 11 year study period. Neonatal mortality fell between 1997-9 and 2006-7 (from 31.4 to 25.1 per 10 000 live births). The relative deprivation gap (ratio of mortality in the most deprived tenth compared with the least deprived tenth) increased from 2.08 in 1997-9 to 2.68 in 2003-5, before a fall to 2.35 in 2006-7. The most common causes of death were immaturity and congenital anomalies. Mortality due to immaturity before 24 weeks' gestation did not decrease over time and showed the widest relative deprivation gap (2.98 in 1997-9; 4.14 in 2003-5; 3.16 in 2006-7). Mortality rates for all other causes fell over time. For congenital anomalies, immaturity, and accidents and other specific causes, the relative deprivation gap widened between 1997-9 and 2003-5, before a slight fall in 2006-7. For intrapartum events and sudden infant deaths (only 13.5% of deaths) the relative deprivation gap narrowed slightly. Conclusions Almost 80% of the relative deprivation gap in all cause mortality was explained by premature birth and congenital anomalies. To reduce socioeconomic inequalities in mortality, a change in focus is needed to concentrate on these two influential causes of death. Understanding the link between deprivation and preterm birth should be a major research priority to identify interventions to reduce preterm birth.